2021
DOI: 10.1097/pcc.0000000000002680
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Severe Sepsis and Shock in Three Asian Countries: A Retrospective Study of Outcomes in Nine PICUs

Abstract: Pediatric sepsis remains a major health problem and is a leading cause of death and long-term disability worldwide. This study aims to characterize epidemiologic, therapeutic, and outcome features of pediatric severe sepsis and septic shock in three Asian countries. DESIGN:A multicenter retrospective study with longitudinal clinical data over 1, 6, 24, 48, and 72 hours of PICU admission. The primary outcome was PICU mortality. Multivariable logistic regression analysis was used to identify factors at PICU admi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…However, there remains a scarcity of recent epidemiological data and only very limited population-based data on pediatric sepsis incidence from South America, Asia, and Africa, where the burden due to sepsis remains highest (10,12,21,25,46). The challenges related to accurate coding of sepsis are further accentuated in neonates, where adjudication of organ dysfunction presents additional difficulties (13,28,34).…”
Section: We Need To Act On Available Data and Improve Data Collectionmentioning
confidence: 99%
“…However, there remains a scarcity of recent epidemiological data and only very limited population-based data on pediatric sepsis incidence from South America, Asia, and Africa, where the burden due to sepsis remains highest (10,12,21,25,46). The challenges related to accurate coding of sepsis are further accentuated in neonates, where adjudication of organ dysfunction presents additional difficulties (13,28,34).…”
Section: We Need To Act On Available Data and Improve Data Collectionmentioning
confidence: 99%
“…Recent multicenter research in an Asian community revealed that the mortality rate for septic shock in children was 19.2%. Before the Surviving Sepsis campaign guidelines were implemented in Thailand, the mortality rate for septic shock among children ranged from 37 to 42 percent [6]. The annual death rate ranged from 231 to 522 per 100,000 persons [7,8].…”
Section: Introductionmentioning
confidence: 99%
“… 1 CAP is a heterogeneous disease that ranges from a mild, self-limited illness to a severe infection that causes respiratory failure, septic shock and even death. 2 According to the data from several population-based studies in different regions, the incidence rate of severe CAP in hospitalized children ranges from 3.9% to 23.0%. 3 , 4 Biomarkers for systemic inflammatory response will provide an objective basis for evaluating the severity of pneumonia.…”
Section: Introductionmentioning
confidence: 99%